Considering 'non-acoustic factors' as social and environmental determinants of health equity and environmental justice. Reflections on research and fields of action towards a vision for environmental noise policies. (September 2021) - Riedel, Natalie; van Kamp, Irene; Dreger, Stefanie; Bolte, Gabriele; Andringa, Tjeerd; Payne, Sarah R.; Schreckenberg, Dirk; Fenech, Benjamin; Lavia, Lisa; Notley, Hilary; Guski, Rainer; Simon, Daniel; et al.
Highlights: Health equity has not been implemented in the European Environmental Noise Directive. Health equity calls for contextualizing exposure-health-relations. 'Non-acoustic factors' can underlie determinants of vulnerability. Perceived environmental control is key to health equity. Actions involve transdisciplinary groundwork, inclusive participation and governance. Abstract: Despite being an overall objective of European policies, health equity and environmental justice have not yet been systematically implemented in environmental policies. Taking control over one's environment as an element of health equity, we consider intractable exposure to transportation noise as a highly relevant policy field. The European Environmental Noise Directive is designed as a sectoral policy dealing with one environmental health determinant (noise) and drawing on the Global Burden of Disease framework, whereas health equity demands an investigation of the manifold variations in the population by combining adverse noise exposure with salutogenetic (psycho-)social and environmental resources. Such resources or the lack thereof have been referred to as 'non-acoustic factors' in noise- and soundscape-related research and can presumably account for vulnerability to transportation noise exposure caused by social and environmental determinants. Thus, we aim to link the current discourse on 'non-acoustic factors' with health equity driven by the need to go beyond average exposure–response-relations. After summarising challenges of environmental noise-related health impact assessment from a health equity perspective, we focus on residents' control – both procedurally and environmentally – to illustrate how social and environmental determinants can cause vulnerability. We advocate to consider 'non-acoustic factors' as leverage to promote health equity and environmental justice through three fields of potential action: (1) developing a theoretical and methodological groundwork and multi/interdisciplinary training of students and professionals, (2) introducing comprehensible information and inclusive participation methods, and (3) creating supportive institutional frames and governance modes. The contents of this paper were derived from a workshop held at the University of Bremen in September 2020.